Live imaging of cysteine-cathepsin activity reveals dynamics of focal inflammation, angiogenesis, and polyp growth. - Elias Gounaris; Ching H Tung; Clifford Restaino; René Maehr; Rainer Kohler; Johanna A Joyce; Hidde L Ploegh; Terrence A Barrett; Ralph Weissleder; Khashayarsha Khazaie (PLoS ONE)
It has been estimated that up to 30% of detectable polyps in patients regress spontaneously. One major challenge in the evaluation of effective therapy of cancer is the readout for tumor regression and favorable biological response to therapy. Inducible near infra-red (NIR) fluorescent probes were utilized to visualize intestinal polyps of mice hemizygous for a novel truncation of the Adenomatous Polyposis coli (APC) gene. Laser Scanning Confocal Microscopy in live mice allowed visualization of cathepsin activity in richly vascularized benign dysplastic lesions. Using biotinylated suicide inhibitors we quantified increased activities of the Cathepsin B & Z in the polyps. More than (3/4) of the probe signal was localized in CD11b(+)Gr1(+) myeloid derived suppressor cells (MDSC) and CD11b(+)F4/80(+) macrophages infiltrating the lesions. Polyposis was attenuated through genetic ablation of cathepsin B, and suppressed by neutralization of TNFalpha in mice. In both cases, diminished probe signal was accounted for by loss of MDSC. Thus, in vivo NIR imaging of focal cathepsin activity reveals inflammatory reactions etiologically linked with cancer progression and is a suitable approach for monitoring response to therapy.